High-risk follicular lymphoma patients: identification and treatment - Luminari, Stefano; Merli, Francesco (European Journal of Oncology and Environmental Health, 2018)
Over the last 15 years, the outcome of patients with follicular lymphoma (FL) has dramatically improved mainly as a result of effective therapies and of a better understanding of lymphoma biology. Although progression-free survival is approximately 10 years with standard treatment and overall survival upwards of 20 years, the clinical behavior among individual patients is highly heterogenous, and a significant number of subjects have a higher and earlier risk of dying from FL within a few years from diagnosis. In this article, we provide an overview of available prognostic tools that can be used to identify high-risk patients with FL and describe which therapies are available and can be recommended for this group of hard-to-treat FL patients.